1995
DOI: 10.3354/meps124105
|View full text |Cite
|
Sign up to set email alerts
|

Structure and dynamics of mussel patches in tidepools on a rocky shore in Nova Scotia, Canada

Abstract: The distribution, size structure, and dynamics of mussel (A4ytllus trossulus, Ad edulis) patches in tidepools were studied on an exposed rocky shore near Halifax. Nova Scotia, Canada. The mussel patches were dynamic, frequently coalescing with one another or disappearing, but mean change in patch area did not vary significantly among seasons or years. Recolonization of areas from which patches were removed occurred slowly, usually by recruitment. Both established and recolonized patches were generally associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 33 publications
(42 reference statements)
3
26
2
Order By: Relevance
“…We found that a high proportion (43 to 100%) of decreases in area of experimental mussel patches over a 15 mo period were not accounted for by in situ mortality (as indicated by empty shells) (Hunt & Scheibling 2001). Also, while monitoring tagged mussels (ca 10 to 15 mm SL) over 3 wk periods, we recorded losses (excluding in situ mortality) consistent with our calculated probabilities of dislodgment: 8% on emergent rock and 16% in tidepools on average in July/ August 1994/95, and 42% on emergent rock and 17% in tidepools in October 1995 when wave heights were greater (Hunt 1997).…”
Section: Discussionsupporting
confidence: 66%
“…We found that a high proportion (43 to 100%) of decreases in area of experimental mussel patches over a 15 mo period were not accounted for by in situ mortality (as indicated by empty shells) (Hunt & Scheibling 2001). Also, while monitoring tagged mussels (ca 10 to 15 mm SL) over 3 wk periods, we recorded losses (excluding in situ mortality) consistent with our calculated probabilities of dislodgment: 8% on emergent rock and 16% in tidepools on average in July/ August 1994/95, and 42% on emergent rock and 17% in tidepools in October 1995 when wave heights were greater (Hunt 1997).…”
Section: Discussionsupporting
confidence: 66%
“…Rock pools are a convenient experimental system because they have well-defined boundaries, are easy to manipulate, have been well studied [36][37][38][39], and are structured by a complex set of physical and biological factors [40]. The study area is a gently sloping rocky platform where ice scouring in spring is an important source of disturbance, dislodging most of the exposed organisms [41].…”
Section: Study Sitementioning
confidence: 99%
“…Supply will have a biogeographic component, but within a given area, hydrodynamic processes can regulate the supply of larvae reaching potential settling sites (Armonies & Hellwig-Armonies 1992, Fuentes & Molares 1994, Leonard et al 1998, Cowen et al 2000, McCulloch & Shanks 2003. Likewise, advection of water/larvae to a site and water flux over a site can influence the number of settlers (Hunt & Scheibling 1995, Judge & Craig 1997, Leonard et al 1998. This implies potential differences in larval supply to wave-exposed as opposed to sheltered sites, and to high as opposed to low shore zones (e.g.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%